The Effect of Zataria multiflora on Clinical, Pulmonary Function, and Oxidant Factors in Patients With Pulmonary Diseases: A Meta‐Analysis of Clinical Trials - Amirali Aali; Erfan Taherifard; Melika Farshidianfar; Farshad Hadianfard; Fatemeh Alamdari; Omid Keshavarzian; Majid Nimrouzi; Seyed Taghi Heydari; Maryam Akbari (Health Science Reports)
ABSTRACT Background and Aims In this study, we investigated the effects of Z. multiflora on clinical presentation, pulmonary function, and inflammatory and oxidative parameters in patients with pulmonary disorders. Methods PubMed, Embase, Web of Science, Scopus, and Cochrane Library databases were searched to identify trials that assessed the effects of Z. multiflora in patients with different pulmonary diseases. A random‐effects model was then applied to estimate the weighted mean differences (WMDs) with 95% confidence intervals (CIs) of the outcomes considered in this meta‐analysis. Additional analyses were performed. Results Eight articles were included in this meta‐analysis. Z. multiflora supplementation was associated with a significant increase in forced vital capacity (15.17%, 95% CI: 11.01–19.33), forced expiratory volume in 1 s (9.22%, 95% CI: 1.73–16.70), peak expiratory flow (8.68%, 95% CI: 5.94–11.42), catalase (0.05 U/mL, 95% CI: 0.01–0.10), thiol (0.02 μmol/mL, 95% CI: 0.01–0.03), interleukin‐10 (0.38 pg/mL, 95% CI: 0.34–0.42) and interferon‐gamma (0.74 pg/mL, 95% CI: 0.56–0.91). Besides, there were significant decreases in chest wheeze (−1.24, 95% CI: −1.48 to 1.01), malondialdehyde (−2.63 nmol/mL, 95% CI: −3.86 to −1.39), and tumor necrosis factor‐alpha levels (−1.45 pg/mL, 95% CI: −2.01 to −0.89). However, there were no significant changes in mid‐maximum expiratory flow and superoxide dismutase levels. Conclusions The current meta‐analysis underscores the effects of Z. multiflora in improving the clinical manifestations of patients with pulmonary disease, as well as its anti‐inflammatory, immunomodulatory, and antioxidant effects. However, more trials with larger samples and longer observation durations are needed to strengthen the evidence for widespread supplementation of Z. multiflora.